A Study on How to Establish the Counter-Drone System for National Crucial Infrastructures - 조상근; 장세진; 김세미 (International Journal of Advanced Culture Technology(IJACT), 2024)
In the Ukraine-Russia war and the Israel-Hamas conflict, drones have become symbols of “overwhelming military superiority,” utilized across tactical and strategic levels for front-line attacks and assaults on critical national facilities. As drone threats intensify, various countries around the world are swiftly establishing “Counter-Drone Systems” to protect critical infrastructure, while North Korea has also unveiled kamikaze drones. The Repulic of Korea is similarly building counter-drone systems focused on protecting national critical infrastructure, yet issues with time synchronization and interoperability have emerged. This study conducted Focus Group Interviews (FGI) with experts from the public, private, and military sectors to identify current issues in the areas of counter-drone system deployment protocols, diversification of counter-drone components, and mobile-based information-sharing systems. Based on these findings, this research aims to organize and optimize a framework for establishing counter-drone systems for critical national infrastructure. Furthermore, we propose this as a methodology for deploying counter-drone systems for essential infrastructure, establishing procedures to effectively respond to evolving drone threats. The procedures outlined in this study require continuous innovation through integrated R&D and training, ensuring real-time responses to increasingly sophisticated drone threats.